ANALISIS WAKTU TUNGGU PELAYANAN APOTIK BPJS RAWAT JALAN DI RUMAH SAKIT X TANJUNGPINANG - Yonrizon Yonrizon; Renatalia Fika; Putri Buana Ningrum (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2025)
Abstract: The quality of prescription services plays a crucial role in determining patient satisfaction with pharmaceutical services. Waiting time is one of the indicators of prescription service quality, as patients tend to feel satisfied when the waiting time for prescription services is not excessively long and meets the established standards. This study is descriptive observational in nature, focusing on a specific sample of outpatient prescriptions at RS X Tanjungpinang. Data were collected through observations during both peak and non-peak hours and analyzed using statistical analysis methods. The results indicate that the average waiting time for non-compounded prescription services during peak and non-peak hours is 8 minutes and 10 seconds. This suggests that RS X Tanjungpinang meets the waiting time standards for prescription services as outlined in Minister of Health Regulation No. 34 of 2016.